Validity of the maximum oxygen deficit accumulated as an index of the anaerobic capacity - J. A. L. Calbet; C. Dorado; J. Sanchis; J. Cortadellas; C. Ferragut (Asociación Española de Ciencias del Deporte, 2010)
To assess the validity of the maximal accumulated oxygen deficit (MAOD) as a measure of the anaerobic capacity, the following variables were determined in twenty nine male Physical Education students: the DMOA, the blood lactate concentration at the end of a exhausting supramaximal bout 120 % VO2max, the maximal and the mean power attained during a Wingate test, and the muscle mass of the legs by dual X-ray absorptiometry. A relationship was found between the MAOD and the blood lactate concentration at the end of the supramaximal bout (r=0.43, p<0.05, n=28). MAOD was also related with both the work performed and the accumulated VO2 achieved during the supramaximal exercise (r=0.59, p<0.001, n=28 y r=0.56, p<0.01, n=29, respectively). The blood lactate concentration at the end of the supramaximal exercise was correlated with the work performed during the supramaximal exercise (r=0.49, p<0.01, n=27). This relationship was stronger after accounting for differences in legs muscle mass (r=0.65, p<0.001, n=26). No relationship was found between MAOD and Wingate maximal and mean power output, even after accounting for differences in legs muscle mass. Neither there was a relationship between the maximal or mean power attained during the Wingate and the blood lactate concentration at the end of the supramaximal exercise. Despite that theoretically the MAOD is the best non-invasive procedure to assess the anaerobic capacity, the weakness of the relationship between MAOD and other variables commonly used in the assessment of the anaerobic qualities limits its interest from a practical perspective. KEY WORDS: Oxygen deficit, anaerobic capacity, performance, validity, fitness.